#### Answer

$y^{13}$

#### Work Step by Step

RECALL:
$\dfrac{a^m}{a^n} = a^{m-n}, a\ne0$
Use the rule above to obtain:
$=y^{19-6}
\\=y^{13}$

Published by
Pearson

ISBN 10:
0-13417-805-X

ISBN 13:
978-0-13417-805-9

$y^{13}$

RECALL:
$\dfrac{a^m}{a^n} = a^{m-n}, a\ne0$
Use the rule above to obtain:
$=y^{19-6}
\\=y^{13}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.